Early essential newborn care in national tertiary hospitals in Cambodia and Lao People's Democratic Republic: a cross-sectional study - Tomomi Kitamura; Hiromi Obara; Mari Honda; Tomoko Mori; Tomoo Ito; Mari Nagai; Sommana Rattana; Tung Rathavy; Yasuo Sugiura (BMC, 2022)
Abstract Background Ministries of health in collaboration with the World Health Organization Regional Office for the Western Pacific (WPRO) have been scaling up early essential newborn care (EENC). This study was carried out to understand current EENC practices at hospitals in two priority countries: the Kingdom of Cambodia (Cambodia) and Lao People's Democratic Republic (Lao PDR). Methods EENC is subdivided into 79 checkpoints, referencing the self-monitoring checklist developed by the WPRO. Each checkpoint is rated using a 0 to 2-point scale, and a percentage was calculated for the rate of practice of each checkpoint by dividing the total scores by the maximum possible scores. Results In total, 55 and 56 deliveries were observed in Cambodia and Lao PDR, respectively, and 35 and 34 normal deliveries were included in the analysis. The overall rates of the practices within the first 15 minutes after birth were high in both countries. The rates of the practices before birth and 15 minutes after birth were lower than the rates of the practices performed within the first 15 minutes after birth, especially "hand wash before preparation", "preparation for newborn resuscitation", and "monitoring of postpartum mothers and babies". A detailed analysis revealed that the quality of the practices differed between the two countries regarding skin-to-skin contact and breastfeeding support. Conclusions The high rates of the practices within the first 15 minutes after birth suggest that the EENC coaching sessions supported by ministries of health and the WPRO have been effective. Differences in the quality of practices performed at a high rate between the two countries appeared to be related to factors such as the timing of the study, the perception of the staff, and the situation at the health facilities. These differences and identified practices with lower rates should be improved according to the situation in each country or health facility. Therefore, determining the quality of the practices in a country or a health facility is important. To further improve the quality of EENC, interventions tailored to the specific situation are necessary.